Is it top-down or bottom-up? an evaluation of processes involved in salience and decision making utilising eye-tracking consumer neuroscience research - Perrott, Rebecca (School of Management Studies, 2025)
Consumers are exposed to vast amounts of visual stimuli on an everyday basis which, due to the brain's limited processing capacity results in insufficient allocation of attention. This can be seen in terms of product advertising as well as packaging including labelling. Bottom-up and top-down visual attention processing, as well as visual saliency, are measured and analysed in neuromarketing research to aid marketers in understanding consumer attention and decision-making. Bottom-up attention refers to attention in response to external factors such as colour, shape and contrast whereas top-down attention is internally motivated in response to a goal or task. Furthermore, visual salience is said to influence bottom-up control and is used by marketers to influence consumer decision-making. Through the use of eye-tracking, a consumer neuroscience tool commonly used to aid the understanding of consumer behaviour and non-conscious cognitive processes such as decision-making, this study has provided useful insights and findings that can be used to aid future market research. A conceptual framework adapted from Wedel & Pieters (2004) and Casado-Aranda et al. (2023) was created to provide a visualisation of the current research proposal. The purpose of this research was to identify the role of top-down and bottom-up attentional processes in consumer decision-making as determined by eye tracking, and in particular, to determine whether bottom-up eye tracking alone can explain consumer decision making. The contribution of bottom-up and top-down visual processes to consumer decision making was also examined. Furthermore, this research assessed the effect of salient objects on both bottom-up and top-down attentional processes within the consumer decision-making processes as well as the impact of salience on free and goal-directed visual search. To address the research questions and objectives the study followed a mixed methods approach combining qualitative and quantitative methods. The research included both self- report methods, eye-tracking technology and DeepGaze IIE software to assess the research framework. The combination of traditional market research techniques and consumer neuroscience technology allowed for the analysis of both conscious and subconscious responses. Respondents completed a questionnaire and three eye-tracking experiments including memorisation and decision-making tasks regarding the advertisements. A target sample of 70 people was restricted to individuals between the ages of 18 and 60 residing in the Cape Town Metropolitan area. Market researchers commonly measure visual attention processes to assess advertisements and packaging. Inconsistent terminology and confusion has provided a need to assess the role of bottom-up and top-down visual attention processes with regard to consumer decision-making. The present study addressed gaps in literature on the role of visual attention in consumer decision-making which can be used by marketers in research and strategy development in respect of the visual attention processes and eye-tracking. The results of this study provided insights into the role of the two visual attention processes and consumer decision making utilising eye-tracking technology. Eye-tracking metrics and heatmaps showed that bottom-up visual attention was not allocated to advertisement features used in decision making. Furthermore, results of both descriptive and inferential statistics indicated top-down visual attention processes plays a significant role in consumer decision-making. Furthermore results of this study operationalised eye-tacking such as Total Fixation Duration (TFD), First Fixation Duration (FFD) and Time to First Fixation (TTFF) with regards to decision-making. Despite the role of the visual attention processes in consumer decision making, eye-tracking and visual attention processes should be used alongside other market research tools to aid understanding of consumer decision-making and navigation of marketing material allowing for a holistic view of eye-tracking and consumer decision making.